TRANSESTERIFIKASI IN SITU BIJI KELOR (Moringa oleifera Lam) MENGGUNAKAN POLIMER BERBAHAN DASAR EUGENOL SEBAGAI PENYANGGA KATALIS H2SO4 - achmad rihday; Erwin Abdul Rahim; Syaiful Bahri; Dwi Juli Pusptasari (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
A study of in situ transesterification of Moringa (Moringa oleifera) seeds with polymer based on eugenol catalyst support have been carried out. The aim of the study is to determine the concentration of eugenol-based polymer support catalyst which was used to produce fatty acid methyl esters with the highest yield, and best time and to determine the composition of fatty acid methyl esters found in transesterification in situ. The results showed that the catalyst concentration of 1% with a reflux time of 150 minutes resulted in a yield of 12.04% methyl ester. The results of analysis of methyl esters using GC-MS contain methyl stearate and methyl-9,12-octadecanoate compounds. The characteristics of methyl ester are water content of 1.23%, acid number of 11.60 mgKOH/gram, saponification number of 0 mg NaOH/gram, and pour point of 16˚C. Keywords: Moringa seed, eugenol as a catalyst support H2SO4, transesterification